Discursos encruzilhados: um estudo do pronunciamento de autoridades de Candomblé em suas relações discursivas sobre a pessoa Trans* - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
The debate on diversity and gender identity has raised questions of various kinds. In this way, this research analyzed how the understanding of the transgender person (Trans*) is constructed within the religious discourse of Candomblé, based on the study of the pronouncement of authority of this religion. In a qualitative approach, Discourse Analysis, in the French line, allowed us to enter the meanings that permeated the discourse itself, together with the decolonial epstemologies, composed the theoretical methodological body of this research. From the analysis of the ideological formations, it was possible to understand that the statements are anchored in meanings such as: the traditionalist discourse that is used to justify the erasure of the Trans*, in the terreiro, through the lack of a history that supports the place of these people within the religious rites as initiates; the separation of religious functions by sex, which is essentially biologizing, or differentiated by bio-logical. Along with the use of modalizers to justify a person's decision to "choose" to be Trans*. "The question of acquired rights" whether they are given by Olódùmarè (the entity of creation) to everyone in the Ayé (the tangible world), employing the idea of free will, or by civil laws that ensure this freedom to justify what he considers to be an option. Thus, transgenderism, as well as transsexuality, are understood as a "choice" within this discourse, in addition to being considered a fact of modernity, without a history that grants them legitimacy. Trans* women are allowed to move around the common spaces as consultants/clients. For this reason, even though Candomblé is a religion that welcomes, as the enunciator says, the category of initiates, which configures an effective link with the terreiro, is erased in this discourse.
Discourses at crossroads: a study of the pronouncements of Candomblé authorities in their discursive relations with Trans* people
Keywords: .; LINGUISTICA, LETRAS E ARTES: LINGUISTICA: TEORIA E ANALISE LINGUISTICA; Análise de discurso; Candomblé; Materialismo histórico; Religião; Transgênero